PENGARUH KEPEMIMPINAN KEPALA DESA DAN MOTIVASI TERHADAP PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN TALUD DAN JALAN DI DESA PINGKUK KECAMATAN JATIROTOKABUPATEN WONOGIRI - Purnomo, Arif (Solidaritas, 2018)
ABSTRACT                This research aims to analyze: (1) the influence of village chief leadership  towards community participation in building talud and roads in the Pingkuk village, Jatiroto Subdistrict, Wonogiri Regency;(2) the influence of motivation on towards community participation in building talud and roads in the Pingkuk Village, Jatiroto Sub-district, Wonogiri Regency; (3) the Influence of village leadership and motivation simultaneously on community participation in the building talud and road in Pingkuk Village, Jatiroto Sub-district, Wonogiri Regency.               This research uses quantitative approach with survey method. The subject of research is the whole community in the village of Pingkuk with a population of 1500. Sampling techniques using Simple Random Sampling. The number of samples used amounted to 306 people. Data collection techniques used were questionnaires. Next test instrument use test validity and reliability tests. Test precondition analysis using a classic assumption test comprising : test test autocorrelation, multicollinearity, normality tests, heteroskedastisitas test. Then test the hypothesis using multiple linear regression.               The results showed;(1)there is a positive and significant influence between the village chiefs leadership on community participation in building talud and roads in Pingkuk Village by 40.9% in a moderate interpretation; (2) there is positive and significant influence between motivation to society participation in building of talud and road in Pingkuk Village 30,3%, in low interpretation; (3) there is positive and significant influence between village head leadership and motivation simultaneously to society participation in the construction of talud and roads in Pingkuk Village, Jatiroto Sub-district, Wonogiri Regency by 34.2%.  Keywords: leadership, motivation, public participation